Twister the dark side of nature - Kennedy, Kathleen; Bont, Jan De ([Burbank, CA] : Universal Pictures, 2000)
Helen Hunt and Bill Paxton play scientists pursuing the most destructive weather front to sweep through mid-America's Tornado Alley in 50 years
VCD format
Keywords: Disaster films